A review for using swarm intelligence in architectural engineering. (June 2022) - Khalil, Randa; El-Kordy, Ahmed; Sobh, Hesham
Swarm intelligence algorithms are natural-inspired computational methods that mimic the social interaction between creatures to solve certain problems. Swarmative computational architecture (SCA) is a novel nomenclature proposed by the authors to present the use of various swarm algorithms in solving architectural problems. It includes three main aspects: form generation/adaptation, performance evaluation, and optimization. This study provides a systematic review and comparative analysis for the major publications within the review scope. The correspondence between dynamic subjects and the objective functions for the optimization process is presented. Particularly, dynamic subjects such as building formation parameters and objective functions such as occupant comfort and energy consumption. The main results and criteria are categorized into the design approach, case study, form generation/adaptation, and performance evaluation/optimization. Finally, this review presents the current trends and highlights the gaps in the use of swarm algorithms to solve architectural engineering problems.